Mucinous Cystic Neoplasms in a Male Patient: Why Could It Be Possible? Case Report - Taffurelli, Giovanni; D’Ambra, Marielda; Pacilio, Carlo Alberto; Buscemi, Salvatore; Panzacchi, Riccardo; Peri, Eugenia; Ricci, Claudio; Santini, Donatella; Pezzilli, Raffaele; Casadei, Riccardo; Minni, Francesco (JOP. Journal of the Pancreas, 2012)
Context Mucinous cystic neoplasms (MCN) of the pancreas concern usually female patients and are characterized by an ovarian-type stroma. Case report A 65-year-old man was admitted to our Institute for the incidental finding, at ultrasonography, of a cystic mass of the body-tail of the pancreas. Laboratory tests, including tumor markers (CEA and CA 19-9), were within normal range. A CT scan confirmed the mass, hypodense, unilocular, 45 mm in diameter, regular shaped and without neither contrast enhancement nor signs of infiltration of adjacent structures. A CWRM showed a well-shaped pancreatic gland with a 49 mm in diameter fluid mass of the body, without septa or endoluminal solid nodules, without a clear communication with the main pancreatic duct. Contrast enhanced-US confirmed a strict connection with the splenic vessels, without infiltration, and revealed the absence of contrast-enhancement as well as the presence of communication with the pancreatic duct. These features suggested an IPMN branch duct type larger than 3 cm. The patient underwent a subtotal pancreatectomy with spleen resection. Pathological examination showed a cystic lesion measuring 40 mm in diameter, with unilocular pattern, smooth and white inner walls, containing viscous whitish mucin and without communication with the main pancreatic duct. Microscopically, the lesion showed two components: a mucinous epithelial layer and a low-grade dysplasia ovarian-type stroma. Tumor cells displayed diffuse positivity for estrogen, progesteron and calretinin. Lymph-nodes (n=6) were negative and surgical margins were tumor-free. A final diagnosis of MCN was performed. Postoperative course was complicated by a pancreatic fistula, grade B, treated with a CT-guided abdominal drainage. The patient was discharged in postoperative day 14 with a minimal residual drainage output and he is alive, disease-free at 6 months after surgery. Conclusion Only 9 cases of MCN have been reported in male patients in literature. Thus, the occurrence of MCN in male patients is very rare and its possible pathogenesis could be referred to embryological abnormalities.